Paediatric clinical examination made easy - Denis Gill; Niall O'Brien (Edinburgh : Elsevier, 2018)
This comprehensive undergraduate medical textbook on the paediatric clinical examination covers not only the medical information, but also advice on dealing with small children, their parents, and breaking bad news
Keywords: Child; Handbooks and manuals; Children Medical examinations; Children Diseases Diagnosis